COMPARATIVE ANALYSIS OF OVEN-DRYING AND KARL FISCHER TITRATION WITH DIFFERENT SOLVENTS FOR WATER DETERMINATION IN EVAPORATED MILK (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
A crucial aspect of every food product’s quality is its water content. The possibility of sample degradation or chemical transformation, as well as the possible loss of volatile chemicals during heating, make it extremely difficult to determine with accuracy. Karl Fischer (KF) titration is one of the most extensively used analytical procedures since it is based on a well-established chemical reaction and has specificity for water. However, in complicated matrices, particularly those that contain both sugars and proteins, even KF titration might produce unreliable findings. Foods often have complex compositions. In many cases they are composed of proteins, sugars, fats, water, and many other constituents. This study evaluates the suitability of two different methods for water content measurement in evaporated milk samples. Two different extraction solutions were used with KF method: solvent - (KF) and boiling methanol -KF (BM). Measuring with solvent as extraction solution was made on two temperatures: room temperature - (KF) and 50 °C - KF (50 °C). Classical heating oven (Oven) was used as reference. Every measurement by KF titration was made in ten replications. Measurements with heating oven were made in five replications. A total of 105 determinations were conducted. For statistical evaluation, descriptive statistics (maximum, minimum, average and standard deviation), correlations and Student´s t-test were used. All methods showed high precision. Comparisons were tested and differences were evaluated at a given confidence level (p < 0.05). There is statistically significant difference between KF (room temperature) and KF (BM) and KF (50°C) and KF (BM). KF and KF (50 °C) did not show statistically significant difference. All methods are in good agreement with heating oven. Classical KF at room temperature is recommended due to comparable precision and shorter analysis time.